FEATURES OF STUDYING THE SECTION "MULTIPLIERS. THE ELEMENTS OF LOGIC" IN THE COURSE OF PRIMARY SCHOOL MATHEMATICS ON THE UPDATED CONTENT OF EDUCATION - Мynzhasarova М.Ж.; Akpaeva А.Б.; Lebedeva Л.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article discusses the features of studying the topics of the section "Set. Elements of Logic" in the course of elementary school mathematics. The analysis of the content of the program and its implementation in the textbook "Mathematics" is given. The article describes the features of the updated content of mathematical education in primary classes. The role of the "Set. Elements of logic" in the development of logical thinking of primary school students. A feature of studying the section "Set. Elements of Logic" is that a system of exercises has been developed that implement the formation of thinking techniques. The analysis of the proposed system of exercises in the implementation of the educational goals of this section is carried out. When developing the system of exercises, the age-specific features of the students ’ thinking development were taken into account. In the organization of work with the system of exercises, the ways of increasing the mental activity of students, the development of independent work were considered. A special role in the development of logical thinking of students is also occupied by logical tasks presented in the category "You are a researcher".